Homocysteine exchange across skeletal muscle in patients with chronic kidney disease. Issue 6 (22nd March 2023) - Garibotto, Giacomo; Picciotto, Daniela; Verzola, Daniela; Valli, Alessando; Sofia, Antonella; Costigliolo, Francesca; Saio, Michela; Viazzi, Francesca; Esposito, Pasquale
Abstract: Sites and mechanisms regulating the supply of homocysteine (Hcy) to the circulation are unexplored in humans. We studied the exchange of Hcy across the forearm in CKD patients ( n  = 17, eGFR 20 ± 2 ml/min), in hemodialysis (HD)‐treated patients ( n  = 14) and controls ( n  = 9). Arterial Hcy was ~ 2.5 folds increased in CKD and HD patients ( p  < 0.05–0.03 vs. controls). Both in controls and in patients Hcy levels in the deep forearm vein were consistently greater (+~7%, p  < 0.05–0.01) than the corresponding arterial levels, indicating the occurrence of Hcy release from muscle. The release of Hcy from the forearm was similar among groups. In all groups arterial Hcy varied with its release from muscle ( p  < 0.03–0.02), suggesting that muscle plays an important role on plasma Hcy levels. Forearm Hcy release was inversely related to folate plasma level in all study groups but neither to vitamin B12 and IL‐6 levels nor to muscle protein net balance. These data indicate that the release of Hcy from peripheral tissue metabolism plays a major role in influencing its Hcy plasma levels in humans and patients with CKD, and that folate is a major determinant of Hcy release. Abstract : Sites and mechanisms underlying the supply of Homocysteine (Hcy) to the circulation are unexplored in humans. Methionine synthase is expressed, although at intermediate level, in skeletal muscle, which, however, represents a large part (about 40%) of body weight. At variance with liver, pancreas and kidney, that express the entire methionine cycle, the transsulfuration pathway is virtually absent in muscle; in addition, even if MTHFR is present in muscle, the methionine remethylation pathway is limited by lack of BHMT. We studied the exchange of Hcy across the forearm (which is mainly composed of muscle) in CKD patients, in hemodialysis (HD)‐treated patients and controls. Arterial Hcy was 2.5 folds increased in CKD and HD patients. Both in controls and in patients Hcy levels in the deep forearm vein were consistently greater (+7%, p  < 0.05–0.01) than the corresponding arterial level, indicating the occurrence of Hcy release from muscle. The release of Hcy from the forearm was similar among groups (−1.8 ± 0.5, −2.1 ± 0.8 and −1.7 ± 0.5 nmol/min). In all groups arterial Hcy varied with its release from muscle, suggesting that muscle plays an important role on plasma Hcy levels. Forearm Hcy release was inversely related to folate level in all study groups. These data indicate that the release of Hcy from peripheral tissue metabolism plays a major role in influencing its plasma levels in humans and patients with CKD, and that folate is a major determinant of Hcy release.